2022
DOI: 10.1136/bmjopen-2021-058233
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 has impacted access to healthcare and social resources among individuals experiencing homelessness in Canada: a scoping review

Abstract: ObjectivesIn Canada, individuals experiencing homelessness (IEH) rely on public health and social services for healthcare, food and basic necessities. The COVID-19 pandemic has disproportionately affected marginalised populations, in part by impacting their access to such services. We performed a scoping review to identify from the published literature how access to services has changed for Canadian IEH during the pandemic.Data sourcesOVID Medline, Web of Science, Sociological Abstracts, CINAHL and OVID EmCare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
1
0
0
Order By: Relevance
“…In line with our findings also other studies revealed positive impacts of the pandemic besides the negative ones mentioned above, like more tranquility and mental space when 24/7 access to shelters is realized, with a limited number of persons per dormitory ( 28 ). There is an urgent need to learn from these often unexpected, positive impacts and see how they can enhance future pandemic responses as well as improve care and support for homeless individuals.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our findings also other studies revealed positive impacts of the pandemic besides the negative ones mentioned above, like more tranquility and mental space when 24/7 access to shelters is realized, with a limited number of persons per dormitory ( 28 ). There is an urgent need to learn from these often unexpected, positive impacts and see how they can enhance future pandemic responses as well as improve care and support for homeless individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Housing is a social determinant of health, and COVID-19 has made it apparent that housing and health are intrinsically interlinked. Nearly five million people in Canada currently live in poverty [ 48 ] and prior to the emergence of COVID-19, Canada was facing a homelessness and housing crisis [ 49 ]. However, the socio-spatial patterning of the virus indicates that such a crisis is not a mere reflection of an irresponsible, failed liberal subjectivity but rather a direct consequence of an institutional failure to accommodate and preserve lives.…”
Section: Discussionmentioning
confidence: 99%